Multilateral Environmental Treaties 2017
DOI: 10.4337/9781783477210.v.16
|View full text |Cite
|
Sign up to set email alerts
|

Convention on the Prevention of Marine Pollution by Dumping of Wastes and Other Matter 1972 and 1996 Protocol

Abstract: In 2008, the governing bodies agreed that a Joint Long-term Programme (JLTP) for the London Convention and Protocol should be prepared that outlines the tasks and activities undertaken by Contracting Parties and their meetings in relation to the two instruments. The JLTP should be updated directly after the session of the governing bodies at the end of each year and would serve as a reference document at the start of the new meetings' season. On this basis, the governing bodies and their subsidiary bodies woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The structure and small sized micro plastics provide high surface to volume ratio, for colonization by microbes. Interaction of micro plastics with microbes affects their sorption and desorption capacity, degradation rate, density and flocculation [14,42,19]. Zettler et al [35] reported different bacterial taxonomic assemblages associating with micro plastics from those in surrounding waters.…”
Section: Interaction Of Micro-plastics With Microbesmentioning
confidence: 99%
“…The structure and small sized micro plastics provide high surface to volume ratio, for colonization by microbes. Interaction of micro plastics with microbes affects their sorption and desorption capacity, degradation rate, density and flocculation [14,42,19]. Zettler et al [35] reported different bacterial taxonomic assemblages associating with micro plastics from those in surrounding waters.…”
Section: Interaction Of Micro-plastics With Microbesmentioning
confidence: 99%
“…Although there is no specific international marine legislation regarding microplastics so far, many proactive countermeasures have been takenvoluntary or legally binding practices at international, regional, and national levels [47]. Indeed, the available literature on marine pollution reports the existence of three global international conventions that deal with the problem of plastic waste in the marine environment at the beginning of the 1970s: [53].…”
Section: Figurementioning
confidence: 99%
“…[to] establish those procedures and mechanisms necessary to assess and promote compliance with [the] Protocol," according to article 11(1) of the 1996 LC&P. 226 In addition, the 29th Consultative Meeting, in 2007, approved the Compliance Group, which monitors obedience by member states. 227 Regarding the effectiveness of the LC&P, it "mainly depends on its capacity to attract participation, in order to foster environmental awareness." 228 Because of that, one of the main downsides of the LC&P is the lack of provisions to solve technical, scientific, and mainly financial obstacles to change the behavior of sea dumping.…”
Section: ] International Law Instruments 895mentioning
confidence: 99%